2015
DOI: 10.1158/1078-0432.ccr-14-2235
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin, NSAIDs, and Risk of Prostate Cancer: Results from the REDUCE Study

Abstract: Purpose A recent meta-analysis showed aspirin was associated with reduced prostate cancer (PC) risk. As anti-inflammatory medications lower PSA levels, whether these findings reflect reduced PC detection or lower PC risk is unknown. We tested the association between aspirin and non-aspirin NSAID on PC diagnosis in REDUCE, where all men received biopsies at 2- and 4-years largely independent of PSA. REDUCE tested dutasteride for PC risk reduction in men with a PSA of 2.5-10.0 ng/mL and a negative pre-study biop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…However, there is no evidence at the cellular levels or in the animal models for such an effect of aspirin on cancer metastasis, even though aspirin is widely used for both the prevention and treatment of many diseases, including cancers in clinical settings (8,(10)(11)(12)(13)(14)9). In this report, we demonstrated that aspirin markedly suppressed the migration and invasion of osteosarcoma cells in vitro, and that Aspirin inhibited the metastasis of osteosarcoma in vivo.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, there is no evidence at the cellular levels or in the animal models for such an effect of aspirin on cancer metastasis, even though aspirin is widely used for both the prevention and treatment of many diseases, including cancers in clinical settings (8,(10)(11)(12)(13)(14)9). In this report, we demonstrated that aspirin markedly suppressed the migration and invasion of osteosarcoma cells in vitro, and that Aspirin inhibited the metastasis of osteosarcoma in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, a recent population study reported that acetylsalicylic acid (aspirin) reduces both the incidence and the risk of metastasis in colon cancer (7). However, there is no evidence at the cellular level or in animal models for such an effect of aspirin on cancer metastasis, even though aspirin is widely used for both the prevention and treatment of many diseases, including cancers in clinical settings (7)(8)(9)(10)(11)(12)(13)(14). In this report, we tried to provide comprehensive evidence at the cellular level and in the animal models to argue that aspirin may be an excellent auxiliary drug for treating patients with osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] In recent years, there has been an increased interest in the antitumour activity of NSAIDs due to at least three reasons: (1) COX-2 is found to be overexpressed in many cancers thus making it an attractive therapeutic target for the prevention and treatment of a number of malignancies [11,12]; (2) chronic inflammation has been proved to play an important role in cancer development and progression [13,14]; (3) NSAIDs are used also by oncology patients and the 'relationships' between these drugs and cancer cells have to be better clarified. [15] Numerous studies have suggested that aspirin and/or other NSAIDs can be effective in the prevention and/or treatment of malignancies, such as cancers of the colon, [16] breast, [17,18] lung, [19] pancreas, [20] prostate, [21,22] ovarium, [23] squamous cell carcinoma and melanoma, [24] etc. Different NSAIDs have been reported to inhibit the growth and survival of cell lines established from a wide variety of cancers, including gastric cancer, [25,26] cancers of the colon, [27] lung, [28] urinary bladder, [29] osteosarcoma, [30] etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain meta-analysis also suggested its association with an increased risk of prostate and other cancer [114] predicting its dubious therapeutic potential which is still needed to be stated adequately in the prospects to develop and use less toxic and economically affordable treatment option for cancer [115].…”
Section: Otc(over the Counter) Nsaids (Non-steroidal Ant Inflammatorymentioning
confidence: 99%